2005
DOI: 10.1258/1357633054461705
|View full text |Cite
|
Sign up to set email alerts
|

Daily usage and efficiency of remote home monitoring in hypertensive patients over a one-year period

Abstract: We evaluated daily self-monitored blood pressure (BP) data collected over one year using remote home monitoring. Fifty treated, moderately hypertensive subjects (26 males, mean age 50 years; 17 females, mean age 54 years; seven exclusions) were recruited for the study in which semi-automatic arm-cuff BP measurement devices were used. The daily self-monitoring regimen had two phases of usage: one of initial enthusiasm (the first one to two months) followed by a phase of lower usage (89% versus 64%, P<0.01). Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
1
20
1
2
Order By: Relevance
“…A lack of motivation was not considered to be a major barrier based on their analysis. 13 In contrast, our study found the most prevalent personal factors affecting nonusage of HBP monitors were forgetting, not having time, and self-described laziness. This suggests HBPM was not a lifestyle priority to subjects, and a lack of motivation does contribute to nonparticipation in HBPM.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…A lack of motivation was not considered to be a major barrier based on their analysis. 13 In contrast, our study found the most prevalent personal factors affecting nonusage of HBP monitors were forgetting, not having time, and self-described laziness. This suggests HBPM was not a lifestyle priority to subjects, and a lack of motivation does contribute to nonparticipation in HBPM.…”
Section: Discussioncontrasting
confidence: 85%
“…Thought they had reported through central system (4) Didn't receive automated reminders (2) System took too long (16) Lost pin/password (6) Never received feedback report (5) Didn't receive response aŌer eliciƟng help from system (3) Concerned over accuracy of cuff (17) Didn't take BPs oŌen enough Concerned over accuracy of cuff (2) Cuff didn't work (14) Didn't know how to use cuff/experienced problems with cuff Didn't know how to use cuff (13) Concerned over accuracy of cuff Disliked cuff (1) Didn't have baƩeries (1) Had normal BP (43) Had normal BP (27) Felt like office readings were sufficient/superior (22) Thought office readings were sufficient/superior (15) Was unaware of reporƟng system (21) Had normal BP (11) Didn't have symptoms of hypertension (9) Didn't know how to report (20) Thought it wasn't important (4) Didn't know how to report (7) Thought office readings were sufficient/superior (11) Had high BP (1) Felt that less frequent monitoring was sufficient (4) Didn't understand the benefit (10) Had too few BPs (1) Didn't know (18) Didn't know (20) Didn't know (9) Other (4) Other (3) Other (3) * n=responses; mulƟple responses allowed for each quesƟon; percentages total more than 100% with a HBP reporting system. We found that the majority of nonreporters (70.2%) still used their HBP cuffs despite not reporting through the central system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…156 A 1-year experience with HBPM combined with telephone transmission to a central server and reports to treating physicians found that initial enthusiasm for HBPM was followed by a decrease in use, so that only 50% preferred to continue HBPM for the second year. 157 A survey comparing patients' attitudes with different methods of obtaining accurate BP measurements found that HBPM was preferred over other methods (which included ABPM and measurement by either the physician or nurse in the office). 158 Will patients want to pay for HBPM as an add-on for management?…”
Section: Cost Of Home Bp Devicesmentioning
confidence: 99%
“…Other studies on the compliance and effectiveness of at home telemonitoring [27] report that over one year compliance rates with recording weight was 75% and for the recording of blood pressure, 90%, whilst another study [28] reports values of 12-75% for compliance with daily weighing for CHF patients. According to Maeder et al, [6], reported levels of compliance varied from approximately 40% to 90%.…”
Section: Introductionmentioning
confidence: 99%